Utilization of Computer Applications in Increasing the Productivity of UMKM in Kendari City (Sagumi) - Sitti Najmia Rifai; Muhammad Akbar Yasin; Muhammad Irwan Syahib; Budi Wijaya Rauf; Ilcham, Ilcham; Dian Puteri Nurbaity; Yudhi Dwi Hartono (Jurnal Pengabdian Pancasila (JPP), 2024)
Micro, Small, and Medium Enterprises (UMKM) play a significant role in Indonesia's economic growth. Sagumi is one of the MSMEs in Kendari City which was founded in 2016 and was witnessed by the President of the FAO (Food Agriculture Organization) Representative of Indonesia. Sales have increased significantly, indicating that there is strong interest and demand for these UMKM products. The challenge faced by Sagumi lies in the lack of application of information and communication technology in operations and marketing which is still manual. One solution to overcome this problem is through holding training for UMKM business actors. Activities are carried out using socialization and direct practice methods. This service activity succeeded in motivating the participants to improve their computer application skills to support productivity and efficiency in operations and marketing.